Characterization of organic constituents in waters and wastewaters of the Athabasca oil sands mining area ... - Strosher, M. T.; Peake, E. (University of Alberta Library, 1978)
The organic constituents of wastewaters discharged from the Great Canadian Oil Sands Ltd. (GCOS) plant and the Syncrude Canada Ltd. lease No. 17 were characterized and compared to those occurring naturally in the Athabasca River. Of the 16 chemical groups investigated in samples of upgrading plant effluent, coke storage area runoff, and Syncrude Canada Ltd. mine depressurization waters, the hydrocarbons, organic sulphur compounds, organic nitrogen compounds, and oxygenated organic compounds were found to be the most abundant constituents. Upgrading plant effluents contained an average of 36 mg/l of organic carbon, of which 17 mg/l was extractable with organic solvents. Organic sulphur compounds comprised 24% of the extractable organic carbon, oxygenated compounds 17%, hydrocarbons 16%, asphaltenes 10%, and nitrogen compounds 7%. Coke storage runoff revealed a total organic carbon content of 25 mg/l, 15 mg/l of which was extractable carbon. The extractable portion contained 18% asphaltenes, 13% oxygenated ...